PROFESSIONAL TRAINING OF SOCIAL EDUCATORS IN TODAY'S CONTEXT (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2025)
Background. In modern conditions, the relevance of rethinking the theoretical foundations and practical mechanisms of professional training of future social pedagogues in institutions of higher and pre-higher education has increased.Methods. The research used the analysis of research sources; synthesis, comparison, systematization, and generalization of information to clarify the state of development of the problem, to determine the conceptual basis of its solution, as well as to highlight the conditions for effectiveness and justify the ways to optimize the professional training of future social pedagogues in the current context.Results. New approaches to the formation of students’ professional readiness for socio-pedagogical work during the war and post-war period in Ukraine have been theoretically substantiated. The principles and sequence of organizing the educational process at various stages of professional training are outlined. Systematic, integrated, and interdisciplinary approaches to organizing the educational process have been further developed. The pedagogical conditions that determine the success of professional training for future social pedagogues have been identified, and ways to optimize it in institutions of higher and pre-higher education have been substantiated.Conclusions. The professional training of future social pedagogues in modern Ukraine faces numerous complex challenges and therefore requires a significant update of its content and mechanisms. The results of the study highlight the need for continued research on various aspects of the professional training of social pedagogues—particularly regarding work with vulnerable populations and the resource provision for this area in institutions of higher and pre-higher education under martial law. Emphasis is placed on the practical significance of the findings for training social pedagogues in the face of today’s socialization challenges.
Keywords: social pedagogue; spheres of influence; social responsibility; professional education; professional competences; components of professional training; improvement of content; optimization of forms